Transforming Higher Education Cooperatives into Digital Cooperatives: A Case Study of KAGUMI and ANGKASA - Reni Rahmawati; Yuniliza; Yesi Elsandra; Erni Febriana Harahap; Laspida; Yulianda Nofika; Adriani; Harisnal (Journal of Community Service and Application of Science, 2025)
The development of digital technology has driven significant changes in the management of cooperatives, including those based in higher education institutions. This article analyzes the transformation of university cooperatives in Indonesia towards a digital cooperative system, with case studies of KAGUMI (Alumni Cooperative of Muhammadiyah University of Indonesia) and ANGKASA (Angkatan Koperasi Kebangsaan Malaysia Berhad). Using a descriptive qualitative approach, data were collected from observations, in-depth interviews, and document studies. The results show that both cooperatives have utilized digitalization in member management, financial transactions, and online reporting. This transformation not only improves efficiency and transparency but also expands services and member participation. This study provides strategic recommendations for other university cooperatives in adopting digital systems in an integrated and sustainable manner.